Hematohidrosis: A rare case of a female child who sweat blood - Geeta Kiran Arakkal; Srishilpa Poojari; G Narasimha Rao Netha; B Udaya Kumar (Wolters Kluwer Medknow Publications, 2017)
Hematohidrosis is a rare clinical entity characterized by excretion of blood in the sweat. Hematohidrosis presents as unpredictable, recurrent episodes of spontaneous and self-limited bloody discharge from the intact skin. Diagnosis of hematohidrosis is confirmed by testing the secretions for the presence of blood components. It is an extremely rare condition, with very few case reports in literature. Herein, we describe a case of hematohidrosis in an 11-year-old female child with pain and tenderness who responded to propranolol.